Family of three under the tree - Douglass, Traci (Harlequin medical romance., 2024)
Radiologist Riley isn’t interested in romance. After an accident left her in a wheelchair, she’ll prove she doesn’t need anyone’s help—especially neurosurgeon Sam’s. But despite his being infuriatingly gorgeous, she can’t knock her new research partner’s commitment to their study. Single dad Sam’s still fighting his grief and is hell-bent on curing the disease that stole his wife. Yet he can’t stop thinking about Riley…or the way his little girl lights up around her. With their undeniable attraction growing, could a family of three top their Christmas lists?